Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Certainly! Let's solve the given equation step-by-step and verify which of the given logarithmic expressions are equivalent solutions.
We start with the given equation:
[tex]\[ 8 e^x - 5 = 0 \][/tex]
1. Isolate the exponential term:
[tex]\[ 8 e^x = 5 \][/tex]
2. Solve for [tex]\( e^x \)[/tex]:
[tex]\[ e^x = \frac{5}{8} \][/tex]
3. Take the natural logarithm of both sides:
[tex]\[ \ln(e^x) = \ln\left(\frac{5}{8}\right) \][/tex]
4. Simplify using properties of logarithms:
[tex]\[ x \ln(e) = \ln\left(\frac{5}{8}\right) \][/tex]
Since [tex]\(\ln(e) = 1\)[/tex], we have:
[tex]\[ x = \ln\left(\frac{5}{8}\right) \][/tex]
So we have:
[tex]\[ x = \ln\left(\frac{5}{8}\right) \][/tex]
Next, let's check the given options to see which ones are equivalent to [tex]\( x = \ln\left(\frac{5}{8}\right) \)[/tex]:
1. [tex]\( x = \ln(5) - \ln(8) \)[/tex]:
Using the property [tex]\(\ln\left(\frac{a}{b}\right) = \ln(a) - \ln(b)\)[/tex], we have:
[tex]\[\ln\left(\frac{5}{8}\right) = \ln(5) - \ln(8)\][/tex]
This is an equivalent expression.
2. [tex]\( x = \ln\left(\frac{5}{8}\right) \)[/tex]:
This is already our derived solution.
This is an equivalent expression.
3. [tex]\( x = \ln(5) + \ln(8) \)[/tex]:
Using the property [tex]\(\ln(ab) = \ln(a) + \ln(b)\)[/tex], we see:
[tex]\[\ln(5) + \ln(8) = \ln(40)\][/tex]
This is not an equivalent expression.
4. [tex]\( x = \frac{\ln(5)}{\ln(8)} \)[/tex]:
This form doesn't represent a valid manipulation of the given equation and has no direct logarithmic property to simplify into the correct form.
This is not an equivalent expression.
5. [tex]\( x = \ln\left(\frac{8}{5}\right) \)[/tex]:
Using the property [tex]\(\ln\left(\frac{a}{b}\right) = \ln(a) - \ln(b)\)[/tex], we have:
[tex]\[\ln\left(\frac{8}{5}\right) = \ln(8) - \ln(5)\][/tex]
This is not an equivalent expression because it represents the inverse ratio.
6. [tex]\( x = \ln(8) - \ln(5) \)[/tex]:
Using the property [tex]\(\ln\left(\frac{a}{b}\right) = \ln(a) - \ln(b)\)[/tex], we see:
[tex]\[\ln(8) - \ln(5) = \ln\left(\frac{8}{5}\right)\][/tex]
This is not an equivalent expression.
So, the correct choices are:
- [tex]\( x = \ln(5) - \ln(8) \)[/tex]
- [tex]\( x = \ln\left(\frac{5}{8}\right) \)[/tex]
The correct options are:
[tex]\[ \boxed{1 \text{ and } 2} \][/tex]
We start with the given equation:
[tex]\[ 8 e^x - 5 = 0 \][/tex]
1. Isolate the exponential term:
[tex]\[ 8 e^x = 5 \][/tex]
2. Solve for [tex]\( e^x \)[/tex]:
[tex]\[ e^x = \frac{5}{8} \][/tex]
3. Take the natural logarithm of both sides:
[tex]\[ \ln(e^x) = \ln\left(\frac{5}{8}\right) \][/tex]
4. Simplify using properties of logarithms:
[tex]\[ x \ln(e) = \ln\left(\frac{5}{8}\right) \][/tex]
Since [tex]\(\ln(e) = 1\)[/tex], we have:
[tex]\[ x = \ln\left(\frac{5}{8}\right) \][/tex]
So we have:
[tex]\[ x = \ln\left(\frac{5}{8}\right) \][/tex]
Next, let's check the given options to see which ones are equivalent to [tex]\( x = \ln\left(\frac{5}{8}\right) \)[/tex]:
1. [tex]\( x = \ln(5) - \ln(8) \)[/tex]:
Using the property [tex]\(\ln\left(\frac{a}{b}\right) = \ln(a) - \ln(b)\)[/tex], we have:
[tex]\[\ln\left(\frac{5}{8}\right) = \ln(5) - \ln(8)\][/tex]
This is an equivalent expression.
2. [tex]\( x = \ln\left(\frac{5}{8}\right) \)[/tex]:
This is already our derived solution.
This is an equivalent expression.
3. [tex]\( x = \ln(5) + \ln(8) \)[/tex]:
Using the property [tex]\(\ln(ab) = \ln(a) + \ln(b)\)[/tex], we see:
[tex]\[\ln(5) + \ln(8) = \ln(40)\][/tex]
This is not an equivalent expression.
4. [tex]\( x = \frac{\ln(5)}{\ln(8)} \)[/tex]:
This form doesn't represent a valid manipulation of the given equation and has no direct logarithmic property to simplify into the correct form.
This is not an equivalent expression.
5. [tex]\( x = \ln\left(\frac{8}{5}\right) \)[/tex]:
Using the property [tex]\(\ln\left(\frac{a}{b}\right) = \ln(a) - \ln(b)\)[/tex], we have:
[tex]\[\ln\left(\frac{8}{5}\right) = \ln(8) - \ln(5)\][/tex]
This is not an equivalent expression because it represents the inverse ratio.
6. [tex]\( x = \ln(8) - \ln(5) \)[/tex]:
Using the property [tex]\(\ln\left(\frac{a}{b}\right) = \ln(a) - \ln(b)\)[/tex], we see:
[tex]\[\ln(8) - \ln(5) = \ln\left(\frac{8}{5}\right)\][/tex]
This is not an equivalent expression.
So, the correct choices are:
- [tex]\( x = \ln(5) - \ln(8) \)[/tex]
- [tex]\( x = \ln\left(\frac{5}{8}\right) \)[/tex]
The correct options are:
[tex]\[ \boxed{1 \text{ and } 2} \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.